Recent findings on the role of wild-type and mutant p53 in cancer development and therapy - Babamohamadi, Mehregan; Babaei, Esmaeil; Ahmed Salih, Burhan; Babamohammadi, Mahshid; Jalal Azeez, Hewa; Othman, Goran (Frontiers in Molecular Biosciences, 2022)
The p53 protein is known as a tumor suppressor protein which is encoded by the TP53 gene consisting of 393 amino acids. This protein responds to various cellular stresses to regulate the expression of target genes, thereby by which causing DNA repair, cell cycle arrest, apoptosis, metabolic changes, and aging. Mutations in TP53 gene and the functions of the wild-type p53 protein (wtp53) have been linked to a variety of human cancers. Eight TP53 gene mutations are located in codons that make up 28% of all p53 mutations. The p53 can be used as a biomarker for tumor progression and a very good target for designing cancer treatment strategies. In wild-type p53-carrying cancers, abnormal signaling of the p53 pathway usually occurs due to other unusual settings, such as high MDM2 expression. These differences between cancer & normal cells have made p53 one of the most important targets for cancer treatment. In this review, we have dealt with various issues such as the relative contribution of wild-type p53 loss of function, including transactivation-dependent and transactivation-independent activities in oncogenic processes and their role in cancer development. We also discuss the role of p53 in the process of ferroptosis and its targeting in cancer treatment. Finally, we focus on p53-related drug delivery systems and investigate the challenges and solutions.